Accuracy of low dose CT in the diagnosis of appendicitis in childhood and comparison with USG and standard dose CT - Dae Yong Yi; Kyung Hoon Lee; Sung Bin Park; Jee Taek Kim; Na Mi Lee; Hyery Kim; Sin Weon Yun; Soo Ahn Chae; In Seok Lim
Abstract Objectives: Computed tomography should be performed after careful consideration due to radiation hazard, which is why interest in low dose CT has increased recently in acute appendicitis. Previous studies have been performed in adult and adolescents populations, but no studies have reported on the efficacy of using low-dose CT in children younger than 10 years. Methods: Patients (n = 475) younger than 10 years who were examined for acute appendicitis were recruited. Subjects were divided into three groups according to the examinations performed: low-dose CT, ultrasonography, and standard-dose CT. Subjects were categorized according to age and body mass index (BMI). Results: Low-dose CT was a contributive tool in diagnosing appendicitis, and it was an adequate method, when compared with ultrasonography and standard-dose CT in terms of sensitivity (95.5% vs. 95.0% and 94.5%, p = 0.794), specificity (94.9% vs. 80.0% and 98.8%, p = 0.024), positive-predictive value (96.4% vs. 92.7% and 97.2%, p = 0.019), and negative-predictive value (93.7% vs. 85.7% and 91.3%, p = 0.890). Low-dose CT accurately diagnosed patients with a perforated appendix. Acute appendicitis was effectively diagnosed using low-dose CT in both early and middle childhood. BMI did not influence the accuracy of detecting acute appendicitis on low-dose CT. Conclusion: Low-dose CT is effective and accurate for diagnosing acute appendicitis in childhood, as well as in adolescents and young adults. Additionally, low-dose CT was relatively accurate, irrespective of age or BMI, for detecting acute appendicitis. Therefore, low-dose CT is recommended for assessing children with suspected acute appendicitis.